Roger Nash Baldwin and the American Civil Liberties Union - Cottrell, Robert C., 1950- (New York : Columbia University Press, 2000)
Roger Nash Baldwin's thirty-year tenure as director of the ACLU marked the period when the modern understanding of the Bill of Rights came into being. Spearheaded by Baldwin, volunteer attorneys of the caliber of Clarence Darrow, Arthur Garfield Hays, Osmond Frankel, and Edward Ennis transformed the constitutional landscape. Company police forces were dismantled. Antievolutionists were discredited (thanks to the Scopes Trial). Censorship of such works as James Joyce's Ulysses was halted. The Scottsboro Boys and Sacco and Vanzetti were defended. The right of free speech for communists and Ku Klux Klansmen alike was upheld, and the foundations were laid for an end to school segregation. Robert Cottrell's magnificent book recaptures the accomplishments and contradictions of the complicated man at the center of these events. Driven, vain, frugal, and tempestuous, America's greatest civil libertarian was initially also a staunch defender of Communist Russia, deferred to the U.S. government over the internment of Japanese Americans, and openly admired J. Edgar Hoover and Douglas MacArthur. His personal relationships were equally complex. Spanning a hundred years from the late 1800s through Baldwin's death in 1981, this riveting biography is an eye-opening view of the development of the American left.
Intro -- Table of Contents -- Preface -- Acknowledgments -- 1. Growing Up in Wellesley Hills -- 2. The Inevitable Harvard and Beyond -- 3. The Progressive as Social Worker -- 4. The Civic League -- 5. Early Civil Liberties Career -- 6. The National Civil Liberties Bureau -- 7. The United States v. Roger Baldwin -- 8. Prison Life -- 9. An Unconventional Marriage -- 10. The American Civil Liberties Union -- 11. The ACLU Under Suspicion -- 12. Turning to the Courts -- 13. International Human Rights -- 14. A European Sabbatical -- 15. Free Speech and the Class Struggle -- 16. From the United Front to the Popular Front -- Illustrations -- 17. The Home Front -- 18. Controversies on the Path from Fellow Traveling to Anticommunism -- 19. Civil Liberties During World War II -- 20. "Quite a Dysfunctional Family'' -- 21. The Cold War, the Shogun, and International Civil Liberties -- 22. A Very Public Retirement in the Age of Anticommunism -- 23. A Man of Contradictions -- 24. Matters of Principle -- 25. The Public Image -- 26. Traveling Hopefully -- Notes -- Collections, Oral Histories, and Interviews -- Bibliography -- Subject Index -- Name Index.
Includes bibliographical references (pages 466-479) and indexes.
Print version record.
JSTOR
Keywords: Baldwin, Roger N. -- 1884-1981.; American Civil Liberties Union -- History; Baldwin, Roger N. -- 1884-1981; American Civil Liberties Union; Civil rights -- United States -- Biography; Civil rights -- United States -- History; Droits de l'homme -- États-Unis -- Biographies; Droits de l'homme -- États-Unis -- Histoire; BIOGRAPHY & AUTOBIOGRAPHY -- Political; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; HISTORY -- United States -- General; Civil rights; United States; Biographies; History; Biographies; Biographies